A low-temperature secondary photocurable grafted oligomer and a photosensitive resin composition containing the same

Through the technical means of low -temperature secondary optical curing widows, it is difficult to achieve efficient optical curing at low temperatures at low temperatures, and realize the effective protection and high -resolution graphics of R, G, B and black matrix in OLEDs in OLED The demand has improved the display effect and yield of OLED.

CN116874659BActive Publication Date: 2025-01-28SHEN ZHEN SHI AN YUN XIN XIN CAI LIAO KE JI YOU XIAN GONG SI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311019054.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-14
Publication Date
2025-01-28
Estimated Expiration
2043-08-14

AI Technical Summary

Technical Problem

OLED displays are prone to damage at high temperatures, and the prior art is difficult to achieve efficient light curing under low temperature conditions, which makes it difficult to meet the requirements of R, G, B and black matrices in OLEDs.

Method used

Using low -temperature two -time light -curing widow cluster, it adopts the aggregation of the resin to the active monomer and the coupling agent at a low degree. Realize deeper cross -linking.

Benefits of technology

The effective protection of R, G, B and the black matrix in OLED, meet the high -resolution graphical needs, and improve the high impedance requirements of ITO coating, and improve the performance and good product rate of OLED.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure FHA0000006500940000011
    Figure FHA0000006500940000011
Patent Text Reader

Abstract

The present invention discloses a low-temperature secondary photocurable grafted oligomer and a photosensitive resin composition containing the same, and relates to the field of organic materials. A low-temperature secondary photocurable grafted oligomer is designed and synthesized, and a photosensitive resin composition prepared by the same is used. The OC layer formed after exposure, development, secondary exposure curing and low-temperature post-baking plays the role of flattening R, G, and B and isolating the influence of oxygen and the next process solvent on the photoresist formed in the previous process, as well as the requirements for insulating ITO plating on the low-temperature OC layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of organic materials, and in particular to a low-temperature secondary photocurable grafted oligomer and a photosensitive resin composition containing the same. Background Art

[0002] Display is the process of converting electrical signals (data information) into visible light (visual information), and the interface that completes the display is the human-machine interface. At present, the most commonly used is the liquid crystal display. The working principle of the liquid crystal display is: under the action of the electric field, the arrangement direction of the liquid crystal molecules changes, the transmittance of the external light source changes (modulation), and the electro-optical conversion is completed. Then, the different excitations of the three primary color signals of R, G, and B are used to complete the color reproduction in the time domain and space domain through the three primary color filters of red, green, and blue. It belongs to passive luminescence and cannot be made flexible.

[0003] Optoelectronic devices that utilize organic materials are becoming increasingly popular for many reasons. Many of the materials used to make such devices are relatively inexpensive, so organic electronic devices have potential cost advantages over inorganic devices. In addition, the inherent properties of organic materials, such as their flexibility, may make them well suited for specialized applications, such as fabrication on flexible substrates. Examples of organic optoelectronic devices include organic light emitting diodes / devices (OLEDs), organic phototransistors, organic photovoltaic cells, and organic photodetectors. For organic light emitting diodes, organic materials may have performance advantages over traditional materials.

[0004] Organic light-emitting diodes use thin organic films that emit light when voltage is applied across the device. OLEDs are becoming an increasingly interesting technology for applications such as flat panel displays, lighting and backlighting. Different materials can emit different amounts of light at a given voltage, and the color gamut is wider than that of LCDs. Organic light-emitting diode (OLED) displays are becoming more and more common, most notably in products such as mobile phones, media players and small entry-level TVs. Unlike standard LCDs, OLED pixels are driven by a current source. Backplane technology enables flexible displays. High-resolution color active-matrix organic light-emitting diode (AMOLED) displays require an active-matrix backplane that uses active switches to switch each pixel on and off. Many companies are now developing organic thin-film transistor (OTFT) backplane processes for flexible displays, which can also be used for OLED displays to enable the introduction of full-color flexible displays. Whether standard or flexible OLED, the same power supply and drive technology are required. OLED displays are a self-luminous display technology that does not require any backlight at all. OLED technology requires a current-controlled drive methodOLEDs have electrical characteristics quite similar to standard light-emitting diodes (LEDs), with brightness depending on the LED current.To turn the OLED on and off and control the OLED current, a control circuit using a thin-film transistor (TFT) is required.

[0005] Since OLED light-emitting materials are organic materials and cannot withstand high temperatures, OLED needs to be coated with a low-temperature organic flat layer (OC) after completing the black matrix (BM) and color filter layers (R, G, B) to ensure the flatness and insulation between BM, R, G, B, and to protect the implementation of each process step without affecting the already completed pixels, as well as the insulation between TFTs. Summary of the invention

[0006] In view of this, one embodiment of the present invention is to provide a low-temperature secondary photocurable grafted oligomer and a composition thereof, wherein under low-illuminance exposure, the resin is polymerized with the active monomer and the coupling agent, and after development and exposure, the epoxy group is polymerized with a cationic initiator under high illumination, so that the composition can be further cross-linked to meet the use requirements of R, G, B and black BM in OLED.

[0007] To achieve the above effects, the low-temperature secondary photocurable grafted oligomer according to the above embodiment has the structure of the following formula I:

[0008]

[0009] Formula I

[0010] Wherein R1 in formula I is methyl or hydrogen, R2 structural unit is a unit with epoxy group such as glycidyl (meth)acrylate, tetrahydrofuran (meth)acrylate, (3-ethyloxetane-3-yl)methyl (meth)acrylate, (2-methyl-2-ethyl-1,3-dioxolan-4-yl)methyl (meth)acrylate, cyclic trimethylolpropane formal (meth)acrylate, (meth)acrylate 2-[(2-tetrahydropyranyl)oxy)]ethyl ester, 1,3-dioxane-(meth)acrylate, preferably glycidyl methacrylate. R3 is methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate or dicyclopentadienyl methacrylate.

[0011] The R2 structural unit is preferably methyl (meth)acrylate or dicyclopentadienyl (meth)acrylate.

[0012] The low-temperature secondary photocuring graft oligomer has an epoxy group molar ratio of 30-70, a hydroxyl group molar ratio of 15-35, and other straight-chain, branched-chain alkyl or aliphatic cycloalkane molar ratio of 15-35.

[0013] More preferably, the low-temperature secondary photocuring grafted oligomer has an acid value of 30-110 mgKOH / g, preferably 40-100 mgKOH / g. If the acid value is too small, there will be residual glue after development. If the acid value exceeds 110 mgKOH / g, the film will fall off. The number average molecular weight is controlled between 2000 and 5000. If the molecular weight is less than 2000, the film is easy to fall off. If the molecular weight is greater than 5000, residual glue is easy to be generated.

[0014] The present invention also discloses a photosensitive resin composition, comprising the above-mentioned low-temperature secondary photocuring grafted oligomer, wherein the components in the photosensitive resin composition are as follows in parts by mass:

[0015] Low temperature secondary light curing grafted oligomer: 5~12 parts

[0016] Coupling agent: 0.1~5 parts

[0017] Leveling agent: 0.3~1 part

[0018] Curing agent: 0.5~5 parts

[0019] Epoxy: 0.5~3 parts

[0020] Photoinitiator: 0.5~1.5 parts

[0021] Cation: 1~3 parts

[0022] Active monomer: 8~15 parts

[0023] PMA: 70~88 copies.

[0024] The curing agent in the above composition can be a latent curing agent, such as blocked amine, melamine resin, anhydride blocked amine, organic hydrazide, modified imidazole, etc., preferably melamine resin.

[0025] The coupling agent in the above composition is a silane, preferably γ-glycidyloxypropyltrimethoxysilane such as KH570 or Dow Corning's Z6030.

[0026] The leveling agent is selected from but not limited to polyether modified polydimethylsiloxane solution, polyester modified polydimethylsiloxane solution, polyether modified polysiloxane solution, polyester modified polymethyl alkylsiloxane solution, polyether modified polydimethylsiloxane solution, polyether modified polydimethylsiloxane solution, polyacrylate solution, fluorocarbon copolymer solution, or a mixture of two or more thereof; the coupling agent is selected from but not limited to N′-β′-aminoethyl-N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane, N′-β′-aminoethyl-N-β- Aminoethyl-γ-aminopropylmethyldimethoxysilane, N′-β′-aminoethyl-N-β-aminoethyl-γ-aminopropylmethyldiethoxysilane, N′-β′-aminoethyl-N-β-aminoethyl-γ-aminopropyltrimethoxysilane, N′-β′-aminoethyl-N-β-aminoethyl-γ-aminopropyltriethoxysilane and N′-β′-aminoethyl-N-β-aminoethyl-α-aminomethyltriethoxysilane, γ-cyclohexylaminopropyltriethoxysilane and methyl, γ-cyclohexylaminopropyldimethoxysilane, γ-chloropropyltriethoxysilane (γ2), one or more thereof. BYK333, BYK378, BYK306, etc. are preferred.

[0027] The solvent in the above composition is a medium polar solvent, and the solvent can be any solvent suitable for dissolving the above-mentioned various components and not chemically reacting. For example, methyl ethyl ketone, ethylene glycol dimethyl ether, 2-ethoxypropanol, 1,4-dioxane, cyclopentanone, propylene glycol methyl ether acetate, propylene glycol monomethyl ether, methyl cellulose acetate, γ-butyrolactone or butyl acetate. Amide solvents such as dimethylformamide, dimethylacetamide, N-methylpyrrolidone, N-ethylpyrrolidone or dimethyl sulfoxide. One solvent can be used alone, or two or more solvents can be mixed and used. The solvent can dissolve other components in the composition well, and make the composition have good coating properties and appropriate drying speed, so the boiling point is between 100°C and 250°C, preferably 120 to 180°C.

[0028] The active monomer in the above composition can be any compound that can react with the low-temperature secondary photocuring graft oligomer. Examples thereof include aromatic vinyl monomers such as styrene, α-methylstyrene, α-chloromethylstyrene, vinyltoluene, divinylbenzene, diallyl phthalate, etc.; polycarboxylic acid monomers such as vinyl acetate and vinyl adipate; methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, ethylene glycol di(meth)acrylate, trimethylolpropane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, etc. These compounds can be used alone or in combination of two or more. Pentaerythritol tetraacrylate or dipentaerythritol hexaacrylate is preferred.

[0029] As the photoinitiator in the above composition, any known compound used for photocuring with active light such as ultraviolet rays can be used without limitation. Specific examples of the photopolymerization initiator include benzoins and their alkyl esters such as benzoin, benzoin methyl ether, and benzoin ethyl ester; acetophenones such as acetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1,1-dichloroacetophenone, and 4-(1-tert-butylperoxy-1-methylethyl)acetophenone; anthracenes such as 2-methylanthraquinone, 2-amylanthraquinone, 2-tert-butylanthraquinone, and 1-chloroanthraquinone; thiazolinones such as 2,4-dimethylthiazolinone, 2,4-diisopropylthiazolinone, and 2-chlorothiazolinone; ketals such as acetophenone dimethyl ketal, 2,2-dimethoxy-2-phenylacetophenone; benzophenones such as 4-(1-tert-butylperoxymethylethyl)benzophenone, 3,3′,4,4′ - benzophenones such as tetra(tert-butylperoxy)benzophenone; 2-methylmethylthio)phenyl]-2-morpholinepropane-1-one and / or 2-benzyl-2-dimethylamino-1-(4-morpholinephenyl)-1-one; acylphosphine oxides and xanthones, OXE-1, OXE-2, etc. These compounds can be used alone or in combination of two or more, preferably OXE-1 (Qiangli Xincai).

[0030] The second photoinitiator is preferably a cationic sulfonium salt.

[0031] The oligomer of the present invention has good cross-linking ability and good compatibility with developer, so when the oligomer is applied to the development process, it can meet the current high-resolution graphics requirements. It can be used for the protection of R, G, B and black matrix in OLED, as well as the subsequent ITO coating. DETAILED DESCRIPTION

[0032] Determination of number average molecular weight:

[0033] Number average molecular weight means the number average molecular weight according to polystyrene measured by GPC method. In the process of determining the number average molecular weight according to polystyrene measured by GPC method, commonly known analytical devices, detectors (such as refractive index detectors) and analytical columns can be used. Commonly applied temperature, solvent and flow conditions can be used. A specific example of measurement conditions is as follows: using Waters PL-GPC220 instrument, using Polymer Laboratories PL gel MIX-B 300mm column at an evaluation temperature of 40 ° C, using tetrahydrofuran as solvent, flow rate of 1mL / min, preparing samples at a concentration of 10mg / 10mL, then feeding in an amount of 200μL, and the calibration curve formed by polystyrene standards can be used to determine the value of Mn. The molecular weight of the polystyrene standards used herein is nine:

[0034] 2000 / 10,000 / 30,000 / 70,000 / 200,000 / 700,000 / 2,000,000 / 4,000,000 / 10,000,000.

[0035] The acid value of the photosensitive graft polymer (A) in the present invention is the number of mg of potassium hydroxide required to neutralize 1 g of photosensitive resin. A certain amount of the reaction solution is weighed and dissolved in a toluene-ethanol mixed solvent, and then measured using a potassium hydroxide ethanol standard titration solution using a Swiss Metrohm potentiometric titrator.

[0036] <Examples and Comparative Examples>

[0037] The following examples are given to explain the embodiments of the present invention in more detail. However, the present invention is not limited to the following examples. In addition, the abbreviations of the raw materials used in the following examples are as follows.

[0038] GMA: Glycidyl Methacrylate

[0039] HEMA: beta-hydroxyethyl methacrylate

[0040] MMA: Methyl Methacrylate

[0041] AIBN: 2,2'-azobisisobutyronitrile

[0042] THPA: Tetrahydrophthalic anhydride

[0043] DCPMA: dicyclopentadienyl methacrylate

[0044] PMA: Propylene glycol monomethyl ether acetate

[0045] Synthesis of oligomers (Synthesis Example A-1):

[0046] Add 28.43g (0.2mol) of GMA, 13.01g of HEMA (0.1mol), 10.01g (0.1mol) of MMA, 2.04g of AIBN, 1.54g of n-dodecyl mercaptan and 50g of PMA to a 250ml three-necked flask, start stirring and pass nitrogen to deoxygenate, pass nitrogen for half an hour. At the same time, add 100g of PMA to a 500ml four-necked flask, install a condenser, thermometer and stir, pass nitrogen to deoxygenate, and heat to 85°. After the temperature in the 500ML flask rises to 85°, pour the mixed monomers in the 250ml flask into the constant pressure funnel and start dripping. The dripping time is controlled at 2.5~3h, and the reaction temperature is controlled at 85±1°. After the dripping is completed, continue the reaction for 2h, sample and test with GPC. After no monomer peak appears in the spectrum, pass air for replacement for 15min.

[0047] Add 15.2 g THPA and 0.152 g MEQH into the above flask, stir for 10 min, then heat to 110° and react for two hours. Stop the reaction when the acid value remains unchanged.

[0048] After GPC detection, the number average Mn is 3230, PDI is 1.68, and the acid value is 84.20 mgKOH / g.

[0049] Synthesis of oligomer (Synthesis Example A-2)

[0050] Add 28.43g (0.2mol) of GMA, 19.52g of HEMA (0.15mol), 5.00g (0.05mol) of MMA, 2.12g of AIBN, 1.59g of n-dodecyl mercaptan and 50g of PMA to a 250ml three-necked flask, start stirring and pass nitrogen to deoxygenate, pass nitrogen for half an hour. At the same time, add 100g of PMA to a 500ml four-necked flask, install a condenser, thermometer and stir, pass nitrogen to deoxygenate, and heat to 85°. After the temperature in the 500ML flask rises to 85°, pour the mixed monomers in the 250ml flask into the constant pressure funnel and start dripping. The dripping time is controlled at 2.5~3h, and the reaction temperature is controlled at 85±1°. After the dripping is completed, continue the reaction for 2h, sample and test with GPC. After no monomer peak appears in the spectrum, pass air for replacement for 15min.

[0051] Add 15.2 g THPA and 0.152 g MEQH into the above flask, stir for 10 min, then heat to 110° and react for two hours. Stop the reaction when the acid value remains unchanged.

[0052] After GPC detection, the number average Mn is 2830, PDI is 1.72, and the acid value is 82.31 mgKOH / g.

[0053] Synthesis of oligomer (Synthesis Example A-3)

[0054] Add 35.54g (0.25mol) of GMA, 13.01g of HEMA (0.1mol), 15.00g (0.15mol) of MMA, 2.26g of AIBN, 1.69g of n-dodecyl mercaptan and 50g of PMA to a 250ml three-necked flask, start stirring and pass nitrogen to deoxygenate for half an hour. At the same time, add 100g of PMA to a 500ml four-necked flask, install a condenser, a thermometer and stir, pass nitrogen to deoxygenate, and heat to 85°. After the temperature in the 500ML flask rises to 85°, pour the mixed monomers in the 250ml flask into the constant pressure funnel and start dripping. The dripping time is controlled at 2.5~3h, and the reaction temperature is controlled at 85±1°. After the dripping is completed, continue the reaction for 2h, sample and test with GPC. After no monomer peak appears in the spectrum, pass air for replacement for 15min.

[0055] 15.2 g THPA and 0.152 g MEQH were added to the flask, stirred for 10 min, and then heated to 110°. The reaction lasted for two hours. The anhydride was measured by infrared at 1770-1850 cm -1 The reaction was stopped when the absorption peak disappeared.

[0056] GPC detection showed that the average Mn was 3680, PDI was 1.75, and the acid value was 71.20 mgKOH / g.

[0057] Oligomer synthesis (Synthesis Example A-4)

[0058] Add 35.53g (0.25mol) of GMA, 19.52g of HEMA (0.15mol), 10.01g (0.1mol) of MMA, 2.60g of AIBN, 1.95g of n-dodecyl mercaptan and 50g of PMA to a 250ml three-necked flask, start stirring and pass nitrogen to deoxygenate for half an hour. At the same time, add 100g of PMA to a 500ml four-necked flask, install a condenser, a thermometer and stir, pass nitrogen to deoxygenate, and heat to 85°. After the temperature in the 500ML flask rises to 85°, pour the mixed monomers in the 250ml flask into the constant pressure funnel and start dripping. The dripping time is controlled at 2.5~3h, and the reaction temperature is controlled at 85±1°. After the dripping is completed, continue the reaction for 2h, sample and test with GPC. After no monomer peak appears in the spectrum, pass air for replacement for 15min.

[0059] Add 22.8 g THPA and 0.228 g MEQH into the above flask, stir for 10 min, then heat to 110° and react for two hours. Stop the reaction when the acid value remains unchanged.

[0060] After GPC detection, the number average Mn is 3040, PDI is 1.78, and the acid value is 95.80 mgKOH / g.

[0061] Oligomer synthesis (Synthesis Example A-5)

[0062] Add 28.43g (0.2mol) of GMA, 13.01g of HEMA (0.1mol), 21.82g (0.1mol) of DCPMA, 2.53g of AIBN, 1.90g of n-dodecyl mercaptan and 50g of PMA to a 250ml three-necked flask, start stirring and pass nitrogen to deoxygenate, pass nitrogen for half an hour. At the same time, add 100g of PMA to a 500ml four-necked flask, install a condenser, thermometer and stir, pass nitrogen to deoxygenate, and heat to 85°. After the temperature in the 500ML flask rises to 85°, pour the mixed monomers in the 250ml flask into the constant pressure funnel and start dripping. The dripping time is controlled at 2.5~3h, and the reaction temperature is controlled at 85±1°. After the dripping is completed, continue the reaction for 2h, sample and test with GPC. After no monomer peak appears in the spectrum, pass air for replacement for 15min.

[0063] Add 15.2 g THPA and 0.152 g MEQH into the above flask, stir for 10 min, then heat to 110° and react for two hours. Stop the reaction when the acid value remains unchanged.

[0064] After GPC detection, the number average Mn is 3140, PDI is 1.65, and the acid value is 71.50 mgKOH / g.

[0065] Oligomer synthesis (Synthesis Example A-6)

[0066] Add 35.53g (0.25mol) of GMA, 13.01g of HEMA (0.1mol), 32.73g (0.15mol) of DCPMA, 3.25g of AIBN, 2.44g of n-dodecyl mercaptan and 50g of PMA to a 250ml three-necked flask, start stirring and pass nitrogen to deoxygenate for half an hour. At the same time, add 100g of PMA to a 500ml four-necked flask, install a condenser, a thermometer and stir, pass nitrogen to deoxygenate, and heat to 85°. After the temperature in the 500ML flask rises to 85°, pour the mixed monomers in the 250ml flask into the constant pressure funnel and start dripping. The dripping time is controlled at 2.5~3h, and the reaction temperature is controlled at 85±1°. After the dripping is completed, continue the reaction for 2h, sample and test with GPC. After no monomer peak appears in the spectrum, pass air for replacement for 15min.

[0067] Add 15.2 g THPA and 0.152 g MEQH into the above flask, stir for 10 min, then heat to 110° and react for two hours. Stop the reaction when the acid value remains unchanged.

[0068] GPC test showed that the average Mn was 4560, PDI was 1.83, and the acid value was 57.60 mgKOH / g.

[0069] Oligomer Comparative Synthesis Example (B-1)

[0070] In a 250 ml three-necked flask, 14.21 g (0.1 mol) of GMA, 26.02 g of HEMA (0.2 mol), 21.82 g (0.10 mol) of DCPMA, 1.24 g of AIBN, 1.86 g of n-dodecyl mercaptan and 50 g of PMA were added. Stirring was started and nitrogen was passed through to deoxygenate for half an hour. At the same time, add 100gPMA to a 500ml four-necked flask, install a condenser, thermometer and stirrer, pass nitrogen to deoxygenate, and raise the temperature to 85°. After the temperature in the 500ML flask rises to 85°, pour the mixed monomers in the 250ml flask into the constant pressure funnel and start adding dropwise. The addition time is controlled at 2.5~3h and the reaction temperature is controlled at 85±1°. After the addition is completed, continue the reaction for 2h. Sampling is tested by GPC. If a monomer peak appears in the spectrum, add 0.2gAIBN and 5mlPMA, and continue the reaction for 1h. After no monomer peak appears in the spectrum, pass air for replacement for 15min.

[0071] Add 30.4 g THPA and 0.30 g MEQH into the above flask, stir for 10 min, then heat to 110° and react for two hours. Stop the reaction when the acid value remains unchanged.

[0072] GPC test showed that the average Mn was 8750, PDI was 1.97, and the acid value was 125.4 mgKOH / g.

[0073] Oligomer Comparative Synthesis Example (B-2)

[0074] In a 250 ml three-necked flask, 42.65 g (0.3 mol) of GMA, 2.6 g of HEMA (0.02 mol), 5.00 g (0.05 mol) of MMA, 1.08 g of AIBN, 1.62 g of n-dodecyl mercaptan and 50 g of PMA were added. Stirring was started and nitrogen was passed through to deoxygenate for half an hour. At the same time, add 100gPMA to a 500ml four-necked flask, install a condenser, thermometer and stirrer, pass nitrogen to deoxygenate, and raise the temperature to 85°. After the temperature in the 500ML flask rises to 85°, pour the mixed monomers in the 250ml flask into the constant pressure funnel and start adding dropwise. The addition time is controlled at 2.5~3h and the reaction temperature is controlled at 85±1°. After the addition is completed, continue the reaction for 2h. Sampling is tested by GPC. If a monomer peak appears in the spectrum, add 0.2gAIBN and 5mlPMA, and continue the reaction for 1h. After no monomer peak appears in the spectrum, pass air for replacement for 15min.

[0075] Add 3.04 g THPA and 0.03 g MEQH into the above flask, stir for 10 min, then heat to 110° and react for two hours. Stop the reaction when the acid value remains unchanged.

[0076] GPC test showed that the average Mn was 9750, PDI was 1.85, and the acid value was 21.02 mgKOH / g.

[0077] Oligomer Comparative Synthesis Example (B-3)

[0078] Add 42.65g (0.3mol) of GMA, 2.6g of HEMA (0.02mol), 10.91g (0.05mol) of DCPMA, 3.25g of AIBN, 2.44g of n-dodecyl mercaptan and 50g of PMA to a 250ml three-necked flask, start stirring and pass nitrogen to deoxygenate, pass nitrogen for half an hour. At the same time, add 100g of PMA to a 500ml four-necked flask, install a condenser, thermometer and stir, pass nitrogen to deoxygenate, and heat to 85°. After the temperature in the 500ML flask rises to 85°, pour the mixed monomers in the 250ml flask into the constant pressure funnel and start dripping. The dripping time is controlled at 2.5~3h, and the reaction temperature is controlled at 85±1°. After the dripping is completed, continue the reaction for 2h, sample and test with GPC. After no monomer peak appears in the spectrum, pass air for replacement for 15min.

[0079] Add 3.04 g THPA and 0.03 g MEQH into the above flask, stir for 10 min, then heat to 110° and react for two hours. Stop the reaction when the acid value remains unchanged.

[0080] The GPC test showed that the average Mn was 8980, the PDI was 2.02, and the acid value was 18.90 mgKOH / g.

[0081] Oligomer Comparative Synthesis Example (B-4)

[0082] In a 250 ml three-necked flask, 56.86 g (0.4 mol) of GMA, 6.5 g of HEMA (0.05 mol), 10.00 g (0.1 mol) of MMA, 1.48 g of AIBN, 2.20 g of n-dodecyl mercaptan and 50 g of PMA were added. Stirring was started and nitrogen was passed through to deoxygenate for half an hour. At the same time, add 100gPMA to a 500ml four-necked flask, install a condenser, thermometer and stirrer, pass nitrogen to deoxygenate, and raise the temperature to 85°. After the temperature in the 500ML flask rises to 85°, pour the mixed monomers in the 250ml flask into the constant pressure funnel and start adding dropwise. The addition time is controlled at 2.5~3h and the reaction temperature is controlled at 85±1°. After the addition is completed, continue to react for 2h, add 5mlPMA solution of 0.3gAIBN, and react for another 2h. Sampling is tested by GPC. After there is no monomer peak in the spectrum, air is introduced for replacement for 15min.

[0083] Add 7.6 g THPA and 0.076 g MEQH into the above flask, stir for 10 min, then heat to 110° and react for two hours. Stop the reaction when the acid value remains unchanged.

[0084] GPC test showed that the average Mn was 7890, PDI was 1.86, and the acid value was 17.80 mgKOH / g.

[0085] Thermal Curing Resin Composition Example A-1

[0086] Oligomer prepared in Synthesis Example A-1: ​​0.9 g

[0087] Coupling agent Z6030 (Dow Corning): 0.05g

[0088] Leveling agent BYK306 (BYK): 0.05g

[0089] Epoxy (Nanya): 0.1g

[0090] Photoinitiator OXE-1 (strong new material): 0.12g

[0091] Cationic sulfonium salt (strong new material): 0.15g

[0092] Active monomer DPHA (Changxing): 1.1g

[0093] PMA: 7.53g

[0094] Subsequent Examples A-2 to A-6 and Comparative Examples B-1 to B-4 were synthesized and prepared by the above method.

[0095] Weigh the above substances into a 20ml brown sample bottle using an analytical balance, use a JOANLAB brand Roller Mixer to homogenize the glue for 3 hours, then use an EZ6-5 vacuum spin coater to spin coat the glue onto a 10×10cm RGB glass film (sample 1), and then spin coat it onto a 10×10cm transparent glass (sample 2), use a Lichen vacuum drying oven to extract the solvent for 180s, then pre-bake it in a 90° Lichen drying oven for 2min, expose it with a mercury lamp exposure machine at a distance of 100μm from the coating film for 2~5s at 60~70mj, develop it with 2.38% TMAH for 70s, then wash off the developer with pure water, dry the water at 85°, expose it with 120~150mj energy under a mercury lamp exposure machine for 10s, and finally dry it in a Lichen hot air drying oven at 85 degrees for 30min, and the dry film thickness reaches 2.3um. After the film is cured and formed, relevant tests are carried out.

[0096] Subsequently, the compositions of Examples A-1 to A-6 and Comparative Examples B-1 to B-4 will be further tested for related properties.

[0097] Alkali developability

[0098] The residue after alkali development was confirmed by observing the pattern after alkali development using a L2030-7045T metallographic microscope. The criteria for this evaluation are as follows.

[0099] ○: No residue

[0100] ×: There is residue

[0101] Table 1 shows the evaluation results of the alkali developability.

[0102] Evaluation of solvent resistance

[0103] The film thickness of the above test film was measured by E-80 film thickness tester (Shenzhen Easy), and then the test piece was placed in a 500mL glass bottle with a cover and 200mL of propylene glycol monomethyl ether acetate was placed and allowed to stand at 25°C. After the above test piece with cured coating was immersed in it, it was allowed to stand for 30 minutes at 25°C. It was taken out and blown dry, and then the film thickness was measured by a film thickness meter. The test results are shown in Table 1.

[0104] ○: Film reduction rate is less than 5%

[0105] ×: Film reduction rate is greater than or equal to 5%

[0106] The test results are shown in Table 1

[0107] Impedance test

[0108] The JF-8030B surface resistance tester (Jingfu, Houjie, Dongguan City) was used to follow the ASTM standard D-257 test method. During the test, two weights were placed on the surface of the object to be measured and the red button was pressed. The specific surface resistance value of the object to be measured will be displayed on the instrument. The test results are shown in Table 1.

[0109] ○: Impedance greater than 10 14 Ω

[0110] ×: Impedance less than 10 14 Ω

[0111] Table 1.

[0112]

[0113] Therefore, the present invention may further provide a resin composition comprising the aforementioned oligomer. In addition to the aforementioned oligomer, the resin composition provided by the present invention may also include a photoinitiator, a curing agent, a solvent and other additives. When the aforementioned oligomer and its composition are used for the protection of R, G, B and black matrix of OLED, while meeting the high impedance requirements of the subsequent ITO coating, and having a very high development resolution, the display effect of OLED can be met and the yield rate can be improved.

[0114] Although the present invention has been disclosed as above in the form of an implementation method, it is not intended to limit the present invention. Any person skilled in the art should be able to make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the scope defined by the attached claims.

Claims

1. A photosensitive resin composition, characterized in that: The components in the photosensitive resin composition are as follows in parts by mass: 8-12 parts of low temperature secondary photocuring grafted oligomer; 0.2-0.5 parts of leveling agent; 0.5 to 1.2 parts of the first photoinitiator; 0.1 to 2 parts of the second photoinitiator; Epoxy 0.5-3 parts; Curing agent 0.5-2 parts; 0.5-3 parts of coupling agent; 5-10 parts of active monomer; 80-90 parts of organic solvent; The low-temperature secondary photocuring grafted oligomer has the structure of the following formula I: Wherein, R1 is methyl or hydrogen, R2 is glycidyl; R3 is methyl or dicyclopentadienyl; The first photoinitiator is OXE-1, and the second photoinitiator is a cationic sulfonium salt.

2. The photosensitive resin composition according to claim 1, characterized in that: The grafted oligomer has an acid value of 30 to 110 mgKOH / g and a number average molecular weight of 2000 to 5000.

3. The photosensitive resin composition according to claim 1, characterized in that: The molar proportion of epoxy groups in the oligomer is 30% to 70%, the molar proportion of hydroxyl groups is 15% to 35%, and the molar proportion of other straight-chain, branched-chain alkyl or aliphatic cycloalkanes is 15% to 35%.

4. The photosensitive resin composition according to claim 1, characterized in that: The solvent is selected from methyl ethyl ketone, ethylene glycol dimethyl ether, 2-ethoxypropanol, 1,4-dioxane, cyclopentanone, propylene glycol methyl ether acetate, propylene glycol monomethyl ether, methyl cellulose acetate, γ-butyrolactone or butyl acetate; one or two of dimethylformamide, dimethylacetamide, N-methylpyrrolidone, N-ethylpyrrolidone or dimethyl sulfoxide, and the boiling point of the solvent is between 100°C and 250°C.

5. The photosensitive resin composition according to claim 1, characterized in that: The curing agent is a latent curing agent, including blocked amines, melamine resins, organic hydrazides, and modified imidazoles.

6. The photosensitive resin composition according to claim 1, characterized in that: The coupling agent is siloxane.

7. The photosensitive resin composition according to claim 1, characterized in that: The active monomer is selected from one or more of styrene, α-methylstyrene, α-chloromethylstyrene, vinyltoluene, divinylbenzene, diallyl phthalate; vinyl acetate, vinyl adipate; methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, ethylene glycol di(meth)acrylate, trimethylolpropane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.

Citation Information

Patent Citations

  • Photosensitive resin composition

    CN111694217A

  • Photosensitive resin composition containing two oligomers and photosensitive spacer

    CN115729043A